Gastrodin reduces myocardial ischemia/reperfusion injury via transgelin2/CNPase-mediated apoptosis regulation - Li, Changyan; Rao, Peng; Liu, Xiang; Yang, Lin; Jiang, Yongliang; Yin, Gaosheng; Li, Shuangxiu; Yang, Ping; Sun, Lin (Frontiers in Pharmacology, 2025)
BackgroundMyocardial ischemia-reperfusion injury (MIRI) frequently occurs during rapid restoration of blood flow in the infarcted myocardium. While Gastrodin (GAS) mitigates MIRI, its mechanism requires further exploration.MethodsWe evaluated GAS effect in SD rats following 45-min left coronary artery ligation and reperfusion. GAS (intraperitoneal) was administered preoperatively for 3 days. Triphenyltetrazolium chloride (TTC) staining was used to detect infarct size. The cardiac function was monitored by the Langendorff isolated cardiac perfusion system. Hematoxylin-Eosin (H&E) staining was applied to detect cardiac injury. H9c2 cells underwent oxygen and glucose deprivation (OGD) and were subsequently restored to normal culture conditions, mimicking MIRI. Cell Counting Kit-8 (CCK-8) was used to detect the cytotoxicity of GAS. Myocardial cell injury was determined by detecting lactate dehydrogenase (LDH) level in the medium. The expression of protein was detected by Western blot (WB) and immunofluorescence (IF) assay. Coimmunocoprecipitation (Co-IP), coupled with molecular docking detected the combination among transgelin2 (TG2), and CNPase.ResultsGAS reduced the size of myocardial infarction, alleviated myocardial fiber damage, and ameliorated MIRI-mediated cardiac dysfunction. Mechanistically, GAS inhibited apoptosis by restoring MIRI-altered TG2/CNPase expression. TG2 directly bound and negatively regulated CNPase. CNPase deficiency enhanced MIRI amelioration by reducing apoptosis.ConclusionTaken together, GAS protects against MIRI by modulating apoptosis through the TG2/CNPase pathway, revealing a novel therapeutic target.